Dispersal, distribution and establishment of arbuscular mycorrhizal fungi: A review - Camargo Ricalde, S.L.
(En, Es)
ilus., 104 ref.
Keywords: HONGOS; MICORRIZAS ARBUSCULARES VESICULARES; DINAMICA DE LA POBLACION; REPRODUCCION; MEXICO; DISPERSION; ESTABLECIMIENTO